Uso do jogo digital “em busca do prêmio nobel” para abordar tópicos de atomística - Diniz, Farnésio Vieira da Silva (Universidade Federal Rural do Semi-Árido, 2018)
An educational product consisting of the use of the game In Search of the Nobel Prize is presented to address topics of atomistics in a public school at Fortaleza, with lowmiddle INSE. The game contains two environments managed by a PHP code. The study environment is open to the public and consists of html pages and conceptual maps on atomistics. The game environment consists of questions similar to those required in various editions of ENEM. Transition screens are associated with each question. Such screens function as the Game Master or Storyteller in RPG games, and simulate the acting of an academic advisor. This communication structure pleased everyone who participated in the project. Socialization activities, with workshops coordinated by the students as they progressed in the game were planned but not executed due to the coincidence of the game schedule with the realization of ENEM. To minimally evaluate this type of activity, when everyone finished the game, an event was held in which each one presented his experience during the game. The event was appreciated by all
Keywords: Ensino de física; Atomística; Modelos atômicos; Jogo digital; Em busca do prêmio nobel; Physics teaching; Atomistics; Atomic models,; Digital game; In search for the nobel prize; CIENCIAS EXATAS E DA TERRA::FISICA